2021
DOI: 10.1007/s10592-021-01369-8
|View full text |Cite
|
Sign up to set email alerts
|

Population genetics and geometric morphometrics of the freshwater snail Segmentina nitida reveal cryptic sympatric species of conservation value in Europe

Abstract: Segmentina nitida Müller 1774 is a rare European freshwater snail of drainage ditches and marshland, which has seen a marked decrease in range (~ 80%) over the last 100 years in the UK. This has been attributed to over-dredging of drainage ditches for land management, conversion of grazing marshes to arable farmland, as well as eutrophication. Segmentina nitida is identified as a priority species in the UK Biodiversity Action Plan (UKBAP) that recommends further research to inform reintroduction and translocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 83 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…on Chichijima Island and other freshwater molluscs. Even with high‐resolution genetic analysis using microsatellites and SNPs, geographic structures on such a narrow scale are usually not detected in other regions (e.g., Hirano et al, 2019; Hobbs et al, 2021; Park et al, 2021). This result might be explained by the fact that Chichijima is topographically steep and has many catchments, whereas continents and larger islands have much larger catchments.…”
Section: Discussionmentioning
confidence: 99%
“…on Chichijima Island and other freshwater molluscs. Even with high‐resolution genetic analysis using microsatellites and SNPs, geographic structures on such a narrow scale are usually not detected in other regions (e.g., Hirano et al, 2019; Hobbs et al, 2021; Park et al, 2021). This result might be explained by the fact that Chichijima is topographically steep and has many catchments, whereas continents and larger islands have much larger catchments.…”
Section: Discussionmentioning
confidence: 99%
“…Since this study was carried out a study (Hobbs et al, 2021) investigating the population structure of S. nitida individuals from Poland, Germany, Sweden and the UK to identify differences both within and between populations has been published. The study found that there are two distinct genetic lineages (also distinct in shape), one in western Europe (UK, Germany -Lineage 1) and one in eastern Europe (Poland, Sweden -Lineage 2).…”
Section: Discussionmentioning
confidence: 99%
“…Since this study was carried out a study [13] investigating the population structure of S. nitida individuals from Poland, Germany, Sweden and the UK to identify differences both within and between populations has been published. The study found that there are two distinct genetic lineages (also distinct in shape), one in western Europe (UK, Germany-Lineage 1) and one in eastern Europe (Poland, Sweden-Lineage 2).…”
Section: Plos Onementioning
confidence: 99%
“…Although once common in the UK, and widespread across lowland England and south Wales, the range of this species has substantially declined since the 1840s [12]. The decline of this species has been attributed to over-dredging of drainage ditches for land management; the conversion of grazing marshes to arable farmland; and eutrophication [13].…”
Section: Introductionmentioning
confidence: 99%